Cooling tower plume abatement using a coaxial plume structure. (May 2018) - Li, Shuo; Moradi, Ali; Vickers, Brad; Flynn, M.R.
Highlights: A novel plume abatement technique using coaxial plume structure is proposed. An analytical model of coaxial (moist) plumes is formulated. The likelihood of fog formation is characterized by resistance factor . Hybrid cooling tower calculation based on ∊ -NTU method is proposed. The operating-environmental condition where coaxial plumes might benefit is examined. Abstract: The traditional approach of cooling tower plume abatement is supposed to result in an unsaturated, well-mixed plume with a "top-hat" structure in the radial structure, but this is an idealization that is rarely achieved in practice. Meanwhile, previous analyses have shown that there may be an advantage in specifically separating the wet and dry air streams whereby the corresponding plume is of the coaxial variety with dry air enveloping (and thereby shielding) an inner core of wet air. Given that a detailed understanding of the evolution of coaxial plumes is presently lacking, we derive an analytical model of coaxial plumes in the atmosphere, which includes the effects of possible condensation. Of particular concern is to properly parameterize the entrainment (by turbulent engulfment) of fluid from the inner to the outer plume and vice versa. We also present and discuss the two different body force formulations that apply in describing the dynamics of the inner plume. Based on the resulting model predictions, we introduce a so-called resistance factor, which is defined as the ratio of the average non-dimensional velocity to the average relative humidity. In the context of visible plume abatement, the resistance factor so defined specifies the likelihood of fog formation and/or a recirculation of moist air into the plenum chamber. On the basis of this analysis, we can identify the region of the operating-environmental condition parameter space where a coaxial plume might offer advantages over its uniform counterpart.